Breath Holding Spells in Children with Long QT Syndrome. (27th April 2015) - Robinson, Jeffrey A.; Bos, J. Martijn; Etheridge, Susan P.; Ackerman, Michael J.
Abstract Background Long QT syndrome (LQTS) is a genetic heart rhythm disorder that may present with syncope, seizures, or sudden cardiac death. Breath holding spells (BHS) occur in 5% of all children and have been noted in children with LQTS anecdotally. The purpose of this study was to determine the frequency of BHS in children diagnosed with LQTS at ≤5 years of age. Design A retrospective review was performed to identify children diagnosed with LQTS who were ≤5 years old at initial presentation to our LQTS clinic from August 1999 to November 2013. The mean length of follow‐up was 6.4 ± 2.8 years. The electronic medical records were reviewed for clinical presentation of BHS, as well as LQTS‐associated symptoms, diagnostic tests, and treatment. Results The study cohort consisted of 115 children with LQTS (58% male; median age at diagnosis, 11 months [range, birth to 5 years]; mean corrected QT interval (QTc), 478 ± 60 milliseconds). At presentation, 80% of patients were asymptomatic. Genetic testing revealed type 1 LQTS (LQT1) in 48%. Overall, 5 of 115 patients (4.3%) had BHS (2 of 5 [40%] male, mean QTc: 492 ± 14 milliseconds, 4 [80%] with family history of LQTS). BHS were the presenting symptom in 1 of 23 symptomatic patients (4.3%). All BHS occurred in patients with LQT1 (P = .02). Conclusions Although BHS among children with LQTS are relatively rare and occur at similar frequency as the general population, they can be the presenting symptom for a heart rhythm disorder. Careful attention to BHS is important to distinguish an innocent BHS from a potential LQTS‐triggered cardiac event so that proper treatment is initiated.